2021
DOI: 10.2176/nmc.st.2021-0230
|View full text |Cite
|
Sign up to set email alerts
|

Current Status and Future Objectives of Surgical Therapies for Epilepsy in Japan

Abstract: This study investigated the number of epilepsy surgeries performed over time in Japan, and conducted a questionnaire survey of the Japan Neurosurgical Society (JNS) training program core hospitals to determine the current status and future objectives of surgical therapies and epilepsy training programs for physicians in Japan. This article presents part of a presentation delivered as a presidential address at the 44th Annual Meeting of the Epilepsy Surgery Society of Japan held in January 2021. The number of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…The survey response rate (17.3%) was not high. Based on the annual reports of the Japan Neurosurgical Society, the total number of epilepsy surgery conducted in Japan between 2015 and 2018 was approximately 1200 per year 26 . In this study, a total of 954 epilepsy surgeries in 1 year were reported (Table 2), which corresponds to 80% of the 1200 surgeries nationwide.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The survey response rate (17.3%) was not high. Based on the annual reports of the Japan Neurosurgical Society, the total number of epilepsy surgery conducted in Japan between 2015 and 2018 was approximately 1200 per year 26 . In this study, a total of 954 epilepsy surgeries in 1 year were reported (Table 2), which corresponds to 80% of the 1200 surgeries nationwide.…”
Section: Discussionmentioning
confidence: 85%
“…Based on the annual reports of the Japan Neurosurgical Society, the total number of epilepsy surgery conducted in Japan between 2015 and 2018 was approximately 1200 per year. 26 In this study, a total of 954 epilepsy surgeries in 1 year were reported (Table 2 ), which corresponds to 80% of the 1200 surgeries nationwide. Besides, since the population of Japan in 2016 was 127 million 27 and the incidence of epilepsy in high‐income countries is 48.86/100 000 person‐year, 1 the estimated number of new cases of epilepsy in Japan is 62 000 per year.…”
Section: Discussionmentioning
confidence: 92%
“…The number of epilepsy surgeries was estimated to be approximately 240 of 100,000 people with medically refractory epilepsy by the 3rd National Database of Health Insurance Claims and Specific Health Checkups of Japan Open Data in 2016, 46) which was remarkably small compared to the number in the report for the United States, 44) although Mikuni et al recently reported that the annual number of epilepsy surgeries in Japan increased from 600 cases in 2011 to 1200 cases in 2018. 47) By contrast, use of the SEEG procedure has just started in Japan. The medical fee revision newly regulated the medical fee points for surgical techniques for SEEG in 2020 in Japan.…”
Section: Current Situation In Japan Regarding Seeg and Associated Issuesmentioning
confidence: 99%
“…This therapy is indicated for patients with resection-unsuitable epilepsy, or as an additional treatment option. [ 3 , 11 , 18 ] VNS can cause stimulation-related adverse effects, including cough, hoarseness, dyspnea, and dysphagia, which are generally well-tolerated. [ 6 , 15 ] The misplacement of electrodes results in the ineffectiveness of therapy, as well as stimulation-induced neck muscle contraction.…”
Section: Introductionmentioning
confidence: 99%